Fundamentals of Sexually Transmitted Infections - Serdaroglu, Server; Kutlubay, Zekayi (IntechOpen, 2017)
This textbook includes the recent progresses and scientific knowledge from the leading experts in different approaches to control, diagnosis, and management depending on resources and facilities available. This book has been written by our colleagues from all over the world. This book is divided into six sections. Each section supplies particularly sexually transmitted infections, diagnostics, microorganism types, pathogenesis, and treatment options. Essential points in publishing this book are to improve our knowledge about sexually transmitted infections and new treatment modalities. One chapter of the book is devoted to viral infections and their treatment. We think that this textbook will serve as a comprehensive guide to many physicians dealing with sexually transmitted infections in their clinical practice. It will hopefully be a precious source for dermatologists, educators, other physicians, and medical students.